2018
DOI: 10.3390/molecules23030559
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Reactivity and Absorption Properties of Melanoidin Blue-G1 through Conceptual DFT

Abstract: This computational study presents the assessment of eleven density functionals that include CAM-B3LYP, LC-wPBE, M11, M11L, MN12L, MN12SX, N12, N12SX, wB97, wB97X and wB97XD related to the Def2TZVP basis sets together with the Solvation Model Density (SMD) solvation model in calculating the molecular properties and structure of the Blue-G1 intermediate melanoidin pigment. The chemical reactivity descriptors for the system are calculated via the conceptual Density Functional Theory (DFT). The choice of the activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(68 citation statements)
references
References 98 publications
(172 reference statements)
2
63
0
Order By: Relevance
“…In the same way, as in our recent works on melanoidins [6][7][8][9][10], it has been found that the model chemistry formed by the connection between the MN12SX density functional and the Def2TZVP basis set is the best for justifying the fulfilling of the KID procedure for the dansylglycine molecule, both in the presence of water and dioxane. is, instead of presenting the comparison of the values of the orbital energies with the ionization potential I and the electron affinity A for different density functionals, we are showing the results for the global descriptors calculated with the MN12SX density functional in Table 1 comparing the values that arise from both solvents.…”
Section: Resultssupporting
confidence: 53%
See 3 more Smart Citations
“…In the same way, as in our recent works on melanoidins [6][7][8][9][10], it has been found that the model chemistry formed by the connection between the MN12SX density functional and the Def2TZVP basis set is the best for justifying the fulfilling of the KID procedure for the dansylglycine molecule, both in the presence of water and dioxane. is, instead of presenting the comparison of the values of the orbital energies with the ionization potential I and the electron affinity A for different density functionals, we are showing the results for the global descriptors calculated with the MN12SX density functional in Table 1 comparing the values that arise from both solvents.…”
Section: Resultssupporting
confidence: 53%
“…Following the lines of our previous work [6][7][8][9][10], the computational studies were performed with the Gaussian 09 [34] series of programs with density functional methods as implemented in the computational package. e basis set used in this work was Def2SVP for geometry optimization and frequencies, while Def2TZVP was considered for the calculation of the electronic properties [35,36].…”
Section: Settings and Computational Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, rather than employing the usual methodology in Medicinal Chemistry research based on Molecular Docking and QSAR and QSPR approximations, we prefer to rely on that mentioned protocol for our research on peptides. Thus, the objective of this work is to study the chemical reactivity of the Leu-Enkephalin opioid peptide neurotransmitter using the techniques of the Conceptual DFT, determining its global properties (of the molecule as a whole) as well as the local properties that allow to understand and predict active reaction sites, both electrophilic and nucleophilic by considering the recent methodology proposed by us [5]- [12]. Likewise, the pKa value of the peptide will be predicted based on a methodology previously developed by us [13], the ability of this potentially therapeutic peptide to act as inhibitor of the formation of Advanced Glycation Endproducts (AGEs) will be established according to our previous ideas [14], and the descriptors of bioavailability and bioactivity (Bioactivity Scores) will be calculated through different procedures described in the literature.…”
Section: Introductionmentioning
confidence: 99%